2016
DOI: 10.1021/acs.energyfuels.6b02264
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Influence of Nanoparticles of Alumina, Copper Oxide, and Zirconium Oxide on the Performance of a Flat-Plate Solar Water Heater

Abstract: In this work, a solar flat-plate collector integrated with four riser tubes having 0.5 m2 area is designed and fabricated. Experiments were conducted using three working nanofluids, namely, alumina, copper oxide, and zirconium oxide, along with the base working fluid water of different weight fractions. The efficiency of collector and storage tank is calculated using the ASHRAE method, and the obtained results were compared. The experimental result shows that alumina nanofluid influences the collector efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Smoke emission increases with load for all tested fuels. As the load increases, additional quantity of fuel is supplied which in turn ends in a richer mixture and leads to higher smoke emissions (Yuvarajan et al 2016). Smoke emissions for MOBDT100, MOBDT200 and MOBDT300 are lower than that for MOBD at all the loads.…”
Section: Smoke Opacitymentioning
confidence: 96%
“…Smoke emission increases with load for all tested fuels. As the load increases, additional quantity of fuel is supplied which in turn ends in a richer mixture and leads to higher smoke emissions (Yuvarajan et al 2016). Smoke emissions for MOBDT100, MOBDT200 and MOBDT300 are lower than that for MOBD at all the loads.…”
Section: Smoke Opacitymentioning
confidence: 96%
“…In recent years, the PV systems had been integrated with techniques such as passive and active control system. 16 They also validated their results with the numerical modelling. Passive system is a technique, which doesn't use any external power for its operation.…”
Section: Introductionmentioning
confidence: 77%
“…used copper and aluminium oxides as the nano additives in three different fashions of 0.1, 0.2, and 0.4 wt%, respectively, and reported that the CuO produces higher thermal efficiency compared with Al 2 O 3. 16 They also validated their results with the numerical modelling. There is a large volume of data on the PV/T system published every year.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations